PENGGUNAAN BATU APUNG DARI KABUPATEN LEMBATA - Hunggurami, Elia; Touselak, Yosafat Sepriyanto; Kumalawati, A. (Jurnal Teknik Sipil, 2013)
The district is an area with the greatest potential pumice in East Nusa Tenggara. Pumice limited usage and the potential availability of the shows that pumice has not been used optimally. Seeing its potential, then another attempt to capitalize on this pumice is used as an alternative to coarse aggregate in normal concrete mix. This will affect the quality of the concrete, so this study aims to determine the compressive strength and split tensile strength of concrete when coarse aggregate in concrete partially substituted by using a pumice stone. Specimens used were as many as 60 concrete cylindrical specimens with 30 MPa compressive strength plan. Pumice stone is used on concrete with substitution of the broken stone. Substitution percentage was 15%, 25%, and 50%. Concrete testing is given 3 different treatment that uses natural pumice stone, pumice stone after the coating as well as the addition of chemicals given in the form of sikafume and sikament Ln. Based on test results, the concrete with substitution levels of 15%, 25%, and 50% lower compressive strength, whereas when given some treatment increases the compressive strength.